Effect of Age on Fatty Acid Composition and Cholesterol Content of Emu (Dromaius novaehollandiae) Meat - Kumar, M. Shasi; kumar, R. Prasanna; kumar, M. Muthu; Reddy, G.V. Bhaskar (Journal of Meat Science, 2015)
The fatty acid composition and cholesterol content of meat of different age groups of emu birds (40, 50, 60 and 70 weeks) were estimated. The overall mean values of palmitic, palmitoleic, stearic, oleic and linoleic acid, total unsaturated fatty acids (% of total fatty acids) and cholesterol content (mg/100g) of emu meat were 23.74 ± 0.17, 6.22 ± 0.17, 9.65 ± 0.13, 42.16 ± 0.30, 19.01 ± 0.49, 67.40 ± 0.21 and 52.81 ± 1.70, respectively. The proportion of palmitic acid, oleic acid, palmitoleic, stearic, linoleic acid and cholesterol content was significantly affected by age (P<0.01). The palmitoleic and oleic acid content is increased with age, while palmitic, linoleic acids were decreased with age. However, age had no significant (P>0.01) effect on the total unsaturated fatty acid content.